How Digital Payment and Online Marketing Strategies affect Consumer Experience in the Culinary Industry? - Rachmawaty Kadir; Andi Naila Quin Azisah Alisyahbana2; Nursinah Amrullah; Ririn Mardhani Syakur; Amraeni Amraeni (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2024)
This study aims to analyze the impact of digital payment and online marketing strategies on the customer experience in the food industry, with a focus on the company